2004
DOI: 10.1002/cncr.20210
|View full text |Cite
|
Sign up to set email alerts
|

Better prediction of prognosis for patients with nasopharyngeal carcinoma using primary tumor volume

Abstract: BACKGROUNDHeterogeneity of primary tumor volume within tumors of the same classification indicates a need to elucidate the effects of primary tumor volume on treatment outcomes in patients with nasopharyngeal carcinoma (NPC).METHODSFrom 1994 through 1996, 129 patients with newly diagnosed NPC who were treated with high‐dose radiotherapy were enrolled in the study. Computed tomography‐derived primary tumor volume was measured using the summation‐of‐area technique. Correlations between American Joint Committee o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 21 publications
7
95
0
Order By: Relevance
“…T-stage, N-stage and metastasis number are all the representations of tumor burden. A lot of articles reported that the greater the tumor load, the worse the prognosis in NPC (Chen et al, 2004;Lee et al, 2008;Chen et al, 2011). Increased number of clonogenic tumor cells is related to tumor hypoxia and possibly alters levels of intercellular communication factors, which are associated with insensitivity to radiotherapy or chemotherapy (Johnson et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…T-stage, N-stage and metastasis number are all the representations of tumor burden. A lot of articles reported that the greater the tumor load, the worse the prognosis in NPC (Chen et al, 2004;Lee et al, 2008;Chen et al, 2011). Increased number of clonogenic tumor cells is related to tumor hypoxia and possibly alters levels of intercellular communication factors, which are associated with insensitivity to radiotherapy or chemotherapy (Johnson et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The possible etiological factors identified for NPC are genetic susceptibility, Epstein-Barr virus (EBV) infection and environmental risk factors. Although plasma EBV DNA quantification has been recommended as an independent biomarker for the prediction of survival (3,4), currently the prediction of prognosis for patients with NPC mainly depends on clinical staging. However, NPC patients with the same clinical stage often present different clinical outcomes, suggesting that the clinical staging is insufficient for accurate prediction of the prognosis of NPC.…”
Section: Introductionmentioning
confidence: 99%
“…NPC is a serious healthcare problem (14), more frequently occurring in Southern China, which presents early metastasis features. At present, radiation therapy is the main NPC treatment.…”
Section: Discussionmentioning
confidence: 99%